2011
DOI: 10.1167/iovs.11-8034
|View full text |Cite
|
Sign up to set email alerts
|

Visual Prognostic Value of Optical Coherence Tomography and Photopic Negative Response in Chiasmal Compression

Abstract: An eye with the more demonstrable structural deterioration, as shown by reduced RNFL thickness and GCC area, and retinal ganglion cell dysfunction as shown by decreased PhNR/b-wave amplitude ratio was associated with the worse visual fields outcome. RNFL thickness and GCC area measurements using OCT and PhNR/b-wave amplitude ratio could be a useful prognostic indicator in the preoperative assessment of chiasmal compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
5
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 26 publications
3
73
5
3
Order By: Relevance
“…This irreversibility of visual outcome in CRP patients may be due to the structural damage of retinal nerve fibers caused by chronic compression of the tumor on anterior optic nerve pathway. 24 …”
Section: Visual Outcomes After Surgery For Craniopharyngiomamentioning
confidence: 99%
“…This irreversibility of visual outcome in CRP patients may be due to the structural damage of retinal nerve fibers caused by chronic compression of the tumor on anterior optic nerve pathway. 24 …”
Section: Visual Outcomes After Surgery For Craniopharyngiomamentioning
confidence: 99%
“…Crossing results in a much smaller contact area between neurons and, therefore, a much greater stress on the crossing fibers for any given compressive force applied to the chiasm (5). Recent studies have looked at factors that can predict outcome after treatment, such as the degree of nerve fiber loss at the optic disc (6,7). A better understanding of the exact mechanism involved has significant implications for management and prognosis and may have more wide-reaching implications for other forms of neural compression involving nerve fibers traveling in different directions (e.g., in the spinal cord).…”
mentioning
confidence: 99%
“…In one study, we have also shown that OCT measurements correlated well both with VF and pattern electroretinogram in patients with chiasmal compression [ 47 ]. Moon et al [ 48 ] showed an important correlation between reduced RNFL thickness and decreased b wave on photopic negative response, both associated with worse VF outcome. Therefore OCT can also be associated with other electrophysiological methods as prognostic indicator in the preoperative assessment of chiasmal compression.…”
Section: Compressive Chiasmal Diseasesmentioning
confidence: 68%